2019
DOI: 10.1177/1070496519888252
|View full text |Cite
|
Sign up to set email alerts
|

Environmental Degradation and Public Opinion: The Case of Air Pollution in Vietnam

Abstract: Air pollution is a pressing problem of public health for developing countries, but governments have few incentives to abate air pollution without public awareness of the issue. Focusing on the case of Vietnam, we examine the determinants of public awareness of air pollution. Using representative survey data for the entire country from 2017, we find that local exposure to air pollution increases public awareness and reduces satisfaction with governments but does not provoke opposition to coal-fired power genera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…The psychological process of migration intention indicates that domestic migration could be highly probable, especially among young and male populations. If the air pollution is not reduced, public awareness towards air pollution will rise [67] and affect the migration choice [42]. Eventually, the domestic migration induced by poor air quality might lead to the relocation of economic forces (male and young people) and hinder the sustainable development in the origin city.…”
Section: Discussionmentioning
confidence: 99%
“…The psychological process of migration intention indicates that domestic migration could be highly probable, especially among young and male populations. If the air pollution is not reduced, public awareness towards air pollution will rise [67] and affect the migration choice [42]. Eventually, the domestic migration induced by poor air quality might lead to the relocation of economic forces (male and young people) and hinder the sustainable development in the origin city.…”
Section: Discussionmentioning
confidence: 99%
“…The government provide various public goods and service to promote public welfare through expenditure. Because environmental quality is of prime importance to human and easily perceived through atmospheric visibility, sensory or health cues, 5 the pollution is more visible and perceptible to residents with a wide range of influence than other public goods. Therefore, the regional environmental quality can be used to measure the effectiveness of local government in public governance and be regarded as a visual indicator to reflect the quality of public service.…”
Section: Relationship Among Public Expenditure Pollution and Subjecti...mentioning
confidence: 99%
“…In other words, as a crucial part of public governance, the pollution has become political and social issues which reflect the efficiency of government governance, not just an environmental problem that affects people's survival and development. 5 That is, there exists the extra costs of environmental degradation. 41 Some research has studied on the political trust in the context of environmental risks, and indicated that the perceived dread of risk made people attribute the causality of the environmental pollution to governments and then impaired public trust in local governments.…”
Section: Relationship Among Public Expenditure Pollution and Subjecti...mentioning
confidence: 99%
“…The extensive application of technology distorts young people's perceptions of the path of ecological destruction, thereby affecting their evaluation of it. Direct exposure to ecological destruction is the basis for personal perception and evaluation [55]. When this perception is interrupted or distorted, evaluation will also be distorted.…”
Section: The "Shielding" Effect Of Technologymentioning
confidence: 99%